Physicochemical properties, biological activities, applications, and protective potential of the skeletal system of Eucommia ulmoides polysaccharides: a review - Liu, Xudong; Xing, Yan; Liu, Guijun; Bao, Dapeng; Zhang, Zhaojiong; Bi, Haizheng; Wang, Meng (Frontiers in Pharmacology, 2025)
Eucommia ulmoides Oliv (E. ulmoides) is a widely distributed plant with economic value, nutritional value, edible value and even medicinal value. In recent years, E. ulmoides polysaccharides are considered to be one of the most important bioactive ingredients in E. ulmoides. Modern pharmacological studies show that the crude extract of E. ulmoides polysaccharides, their active monomer and ramifications have a wide range of pharmacological activities in vitro and in vivo experiments, which can be used to improve inflammation, regulate immunity, improve osteoporosis, and promote osseointegration, etc. Therefore, this review focuses on the induction and summary of the research at home and abroad in recent years, and summarizes the extraction and purification, modification methods, physicochemical properties, biological activities and potential mechanisms of E. ulmoides polysaccharides, providing a theoretical basis for the in-depth study of E. ulmoides polysaccharides and the development of related products.